The utilization bound of uniprocessor preemptive slack-monotonic scheduling is 50% - Andersson, Björn (2014)
Consider the problem of scheduling a set of sporadically arriving implicit-deadline tasks to meet deadlines on a uniprocessor. Static-priority scheduling is considered using the slack-monotonic priority-assignment scheme. We prove that its utilization bound is 50%.